Selling and Sales Management - David Jobber; Geoffrey Lancaster; Kenneth Le Meunier-FitzHugh (United Kingdom Pearson, 2019)
Over the last twenty years, "Selling and Sales Management "has proved itself to be the definitive text in this exciting and fast-moving area. This new edition comes fully updated with brand new case studies using working businesses to connect sales theory to the practical implications of selling in a modern environment.
Keywords: Selling; Sales management; (HRM3045-N) Strategic Management and Responsible Leadership